2014
DOI: 10.1108/jd-02-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive styles and the use of electronic journals in a mobile context

Abstract: Purpose -The purpose of this paper is to examine how different cognitive style groups use electronic journals via mobile devices, with an emphasis on the use of search mechanisms, the approaches to judge the relevance and to refine the results, the use of horizontal screens, and on the influence of negative emotions. Design/methodology/approach -Participants' cognitive styles were identified as Holists and Serialists with Ford's Study Preference Questionnaire. The behaviour of the participants interacting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Specifically, research findings have correlated field dependence-independence with Baddeley's visuospatial sketchpad and central executive system [Baddeley, 1992;2012], since viewing shapes is primarily a visuospatial function, and the cognitive ability of extracting embedded shapes out of a complex whole involves the use of central executive functions, such as monitoring [Angeli et al, 2009]. Furthermore, a considerable number of studies confirmed that field dependence-independence affects search and browsing behavior of users in interactive systems [Chan et al, 2014;Kinley et al, 2014;Belk et al, 2013;Chen and Liu, 2008;Clewley et al, 2011;2010], problem solving performance in educational and hypermedia environments [Angeli et al, 2004;2013], gaming performance and behavior in cultural heritage games [Raptis et al, 2016], and digital-based puzzle problems [Hong et al, 2012].…”
Section: Background Theory and Motivationmentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, research findings have correlated field dependence-independence with Baddeley's visuospatial sketchpad and central executive system [Baddeley, 1992;2012], since viewing shapes is primarily a visuospatial function, and the cognitive ability of extracting embedded shapes out of a complex whole involves the use of central executive functions, such as monitoring [Angeli et al, 2009]. Furthermore, a considerable number of studies confirmed that field dependence-independence affects search and browsing behavior of users in interactive systems [Chan et al, 2014;Kinley et al, 2014;Belk et al, 2013;Chen and Liu, 2008;Clewley et al, 2011;2010], problem solving performance in educational and hypermedia environments [Angeli et al, 2004;2013], gaming performance and behavior in cultural heritage games [Raptis et al, 2016], and digital-based puzzle problems [Hong et al, 2012].…”
Section: Background Theory and Motivationmentioning
confidence: 95%
“…Such methods would increase user acceptance of the approach since the field dependence-independence characteristics could be transparently elicited based on the users' interactions with the system, without requiring to conduct any additional psychometric tests that would add a burden to the users. Accordingly, the users' field dependence-independence characteristics could be implicitly inferred by tracking their behavior with navigation tools [Chen and Liu, 2008], or based on the usage of search tools [Chan et al, 2014].…”
mentioning
confidence: 99%
“…The Wholist/Analyst cognitive style distinguishes individuals as Wholists that prefer and tend to structure incoming information as a whole to get the big picture, and experience surroundings of the environment in a relative passive and global manner, or as Analysts that prefer and tend to structure the incoming info rmation in detail, and experience surroundings in an active manner and with an internal perspe ctive. A high number of studies which investigated the effect of cognitive styles on users' task usability and interaction patterns within Web environments, revealed implications of cognitive styles on users' performance and preferred ways of using different navigation tools and display options [13,14,15]. On the contrary, various studies concluded that cognitive styles do not have a main effect on users' task performance and preference within hypermedia environments [16].…”
Section: Individual Differences In Cognitive Stylesmentioning
confidence: 99%
“…Such methods would increase user acceptance of the approach since the cognitive characteristics could be transparently elicited based on the users' interactions with the system, without requiring to conduct any additional psychometric tests that would add a burden to the users. Accordingly, the users' cognitive characteristics could be implicitly inferred by tracking their navigation sequence in particular sections of the system (Belk et al, 2013), by tracking their behavior with navigation tools (hierarchical maps or alphabetical index) (Chen and Liu, 2008), or based on the usage of search tools (basic or advanced search) (Chan et al, 2014).…”
Section: Validity and Limitationsmentioning
confidence: 99%